The productivity of spring wheat (Triticum aestivum L.) on the autumn sowing date - Wyzińska, Marta; Grabiński, Jerzy (Polish Journal of Agronomy, 2020)
There are not many results of studies concerning the effect of autumn sowing date on the yield of spring cereal cultivars. Due to the fact that meteorological conditions in winter have become milder, the sowing of spring varieties with increased frost resistance is possible in autumn. Spring varieties suitable for autumn sowing are known as alternative varieties. The aim of the research was to determine the effect of autumn sowing date on the productivity of selected spring varieties. A two-factor field experiment was established using a split-plot design at the Experimental Station of Cultivar Testing in Czesławice (51°30′N 22°24′E), the Lubelskie voivodeship, Poland (2008/2009, 2009/2010, 2010/2011). Experimental factors were as follows: A) sowing date: I – October, II – November, III – spring, B) spring wheat cultivar: Tybalt, Cytra, Bombona, Monsun, Parabola. In the first year of the study, no effect of sowing date on spring wheat yields was found. In subsequent growing seasons, both autumn sowing dates had a positive effect on the yields of the tested spring wheat varieties. The selection of the cultivar did not affect the obtained yields.